2017
DOI: 10.18178/ijcea.2017.8.5.675
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Multiple Emulsions as Platforms for Targeted Drug Delivery

Abstract: Abstract-The paper presents the results of modification of outer interfaces of oil drops of multiple emulsions W 1 /O/W 2 for targeted drug delivery. The modification involves physical adsorption of antibodies: anti-CD15 (Hodgkin's disease marker). The effect of molecular interaction between molecules of antibody (protein) and oil phase compounds was measured using isothermal titration calorimetry (ITC). The ITC analysis also included investigation of interactions between components of emulsion and antibody bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…The obtained nanoparticles demonstrated an excellent loading and release of doxorubicin hydrochloride, which was quick in a weakly acidic environment but slightly slow in the basic media. In addition, multiple emulsions composed of an alginic acid solution as inner phase, water, and soybean oil as membrane phase were used as platforms to deliver doxorubicin and temozolomide in drug delivery application. Besides, studies have shown that the effectiveness of cancer chemotherapy treatment efficiency could be increased.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained nanoparticles demonstrated an excellent loading and release of doxorubicin hydrochloride, which was quick in a weakly acidic environment but slightly slow in the basic media. In addition, multiple emulsions composed of an alginic acid solution as inner phase, water, and soybean oil as membrane phase were used as platforms to deliver doxorubicin and temozolomide in drug delivery application. Besides, studies have shown that the effectiveness of cancer chemotherapy treatment efficiency could be increased.…”
Section: Introductionmentioning
confidence: 99%